ANALISIS KUAT TARIK 'UNTENSIONED CABLE BOLT' DI BADAN BIJIH KUBANG CICAU BERDASARKAN UJI LABORATORIUM - O. Erlangga (NIM 22198014), Endri
Abstract : Apart of cable element strength and length of anchoring, there are 3 (three) performance parameter of cable bolt reinforcement, namely; grout strength, rock strength and cable bolt installation parameter. The use of Conbextra GP cement as grout with water:cement ratios 0.4 (by weight), can cause various grout strength along bore hole columns. This case was made by the present of segregation between grouts dominated by Quartz Sand underlying beneath and the more liquid grout at the upper part with stronger UCS and Modullus to compare with the lower grout. Apart of that, ratios of water : cement 0,4 (by weight), cause grout in liquid phase, Thus, at the grouting processes in the field, in part of grout went into joint aperture. Pull out test of cable bolt at the Laboratory showed that grout strength influence the pull out force of cable. Laboratory Test I & 11 used segregated grout (?c = 13 - 24 MPa), so the total grout strength seemed weaker than grout of Laboratory Test Ill (?c = 24 MPa). The pull out of Laboratory Test III resulted, that the more strength of grout, the more power was needed to pull out the cable ( Lab.Test I & II = 9 ton, Lab. Test III = 12 ton). However at the strength of grout with UCS = 24 MPa & Modullus 5.5 GPa, there was no influence from rock confinement. At this research, the increase of confining concrete strength has no role in increasing the pull out strength. This might be cause that weak grout strength have no opportunity to develop it strength to radial direction. Thus, grout was easy to failure when pulling out the cable. Apart of that, the use of grout with water : cement ratios 0,4 (by weight) had cause significance bleeding which finally made pull out strength become weaker.